PERFORMANCE EVALUATION: An intervening model of job satisfaction, transformational leadership and career development - Muhammad Zuhri; Rahmi Fahmy; Hendra Lukito (Halu Oleo University, 2023)
This study aims to examine the performance of academic staff through an evaluating model mediation of transformational leadership, career development, and job satisfaction. Recorded, eighty-five respondents have participated in this study to help institutional development. By the assistance of Smart-PLS software to the feedback data, result shows that transformational leadership isn’t significant to performance and job satisfaction, while career development was found significant effect on job satisfaction but not performance. Mediating contribution of job satisfaction stated partial effects on both, but only enhance relationship between career development and performance.